2014
DOI: 10.3109/10826084.2014.914373
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing and Comparing the Association Between Control Policy Measures and Alcohol Consumption in Europe

Abstract: This paper focuses on the association between alcohol consumption and the introduction of control policy measures, within the AMPHORA 12 country European project. We estimated the "net" associations between intervention policies and total alcohol consumption, taking into account contextual socioeconomic factors and including all policies in the same regression model. The associations were estimated for each country, and the country-specific results were compared in a random-effects meta-analysis. The associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…found that stricter marketing regulations were associated cross‐sectionally with a low prevalence of hazardous drinking among 50–64‐year‐olds in 16 European countries . Examining a range of alcohol control policies, including alcohol advertising restrictions, from the 1960s to the 2000s, Baccini & Carreras found a significant decrease in consumption following advertisement restrictions only in France and not in five other countries where restrictions were implemented during the study period . Smith & Geller found 32.9% fewer youth traffic fatalities in US states with laws prohibiting alcohol advertising targeting minors compared with states lacking such laws.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…found that stricter marketing regulations were associated cross‐sectionally with a low prevalence of hazardous drinking among 50–64‐year‐olds in 16 European countries . Examining a range of alcohol control policies, including alcohol advertising restrictions, from the 1960s to the 2000s, Baccini & Carreras found a significant decrease in consumption following advertisement restrictions only in France and not in five other countries where restrictions were implemented during the study period . Smith & Geller found 32.9% fewer youth traffic fatalities in US states with laws prohibiting alcohol advertising targeting minors compared with states lacking such laws.…”
Section: Discussionmentioning
confidence: 97%
“…This suggests that future longitudinal research should measure branded exposure and consumption. Moreover, Ross and colleagues have argued that the relationship between youth exposure to alcohol marketing and youth drinking initiation is non‐linear, with saturation beginning to occur at higher levels of exposure. This also has implications for future research.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, specifying the same regression model in each country (in particular in the European level analysis), we avoided possible heterogeneity among country-specific estimates due to differences in model specification or explanatory variables choice. This favored the second step of the analysis, consisting in comparison among countries (see the paper in the same issue by Baccini & Carreras, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…The complete results are presented in the paper by Allamani, Pepe, Baccini, Massini, and Voller (2014) and in the paper by Baccini & Carreras (2014), where a description of the meta-analysis model adopted to combine the country-specific findings is also provided.…”
Section: Introductionmentioning
confidence: 98%
“…En este sentido los indicadores de potencia, dosis, ventas de cannabis, producción legal y daños asociados al cannabis (accidentes de tráfico, visitas a urgencias, atención especializada del trastorno por uso de cannabis, prevalencia del consumo en pacientes de salud mental y justicia) deben ser tenidos en cuenta (Hall, 2017). Por último, probablemente unas políticas públicas basadas en las Three Best Buys (limitación de acceso a la sustancia, limitación de la publicidad e incremento del precio a través de medidas impositivas o precio mínimo por unidad de consumo) (Baccini y Carreras, 2014;Matrai et al, 2014) tendría sentido para aproximarnos al modelo contemporáneo de prevención del tabaquismo y alejarnos del modelo poco eficaz y heterogéneo de prevención de las consecuencias del consumo de alcohol. Esto quiere decir evitar poner en manos de la naciente industria del cannabis las medidas de prevención bajo el lema "consumo responsable" y asumir estrategias de prevención basadas en la evidencia.…”
Section: ¿Qué Sabemos Y Qué No Sabemos Del Daño Causado Por El Cannabis?unclassified